Ocular Injuries and Intimate Partner Violence: A Review of the Literature - Baldwin G; Miller JB (Clinical Ophthalmology)
Grace Baldwin, John B Miller Retina Service, Massachusetts Eye and Ear, Department of Ophthalmology, Harvard Medical School, Boston, MA, USACorrespondence: John B Miller, Retina Service, Massachusetts Eye and Ear, Department of Ophthalmology, Harvard Medical School, Harvard Retinal Imaging Lab, 243 Charles St, Boston, MA, 02114, USA, Tel +1 (617) 573-3750, Fax +1 (617) 573-3698, Email John_Miller@meei.harvard.eduPurpose of Review: Intimate partner violence (IPV) is a leading cause of death and disability across the world. We sought to investigate the prevalence and clinical presentation of ocular injuries in IPV.Recent Findings: Literature review revealed 16 published studies that evaluated ocular injuries in IPV, of which the study types included 9 retrospective studies, 2 prospective, 1 review, 1 invited commentary, 2 case reports, and 1 population-based cross-sectional survey. These studies suggest that 45% of IPV incidents involve ocular injury. Various injury types have been described including traumatic cataract, dislocated lens, retinal detachment, intraocular hemorrhage, orbital and zygomaticomaxillary complex fractures, optic nerve avulsion, and open globe injuries. Implementation of IPV screening programs in various clinical settings, including an emergency department evaluating ocular trauma, suggests a positive association with identification of IPV and improving access to resources.Summary: Within IPV, ocular injuries are a prevalent and important cause of vision loss. Various injuries have been reported affecting nearly every anatomical region of the eye. Routine screening for IPV among patients that present with ocular injuries and evaluating for visual complaints among patients experiencing IPV are both important. Future work focused on prospective studies and evaluation of screening techniques may be impactful.Keywords: intimate partner violence, ocular injuries, trauma